2021
DOI: 10.1113/jp281730
|View full text |Cite
|
Sign up to set email alerts
|

Global REACH 2018: the adaptive phenotype to life with chronic mountain sickness and polycythaemia

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 76 publications
(97 reference statements)
5
12
0
Order By: Relevance
“…50—60% in healthy high-altitude residents, which is much higher than our corresponding finding (+23%; Table 3 ), while ( Oberholzer et al, 2020 ) showed a similar result (+17%) in residents at the same altitude as that of our study. Additionally, Claydon et al (2004) and Hansen et al (2021) reported absolute data similar to those in our study in high-altitude residents, but unfortunately, they did not present data for a SL control group. It is possible that intoxication with cobalt from the surrounding cobalt mines augments hypoxia-mediated erythropoiesis ( Jefferson et al, 2002 ) and contributes to the excessive erythrocytosis described by Lawrence et al (1952) and Hurtado (1960) .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…50—60% in healthy high-altitude residents, which is much higher than our corresponding finding (+23%; Table 3 ), while ( Oberholzer et al, 2020 ) showed a similar result (+17%) in residents at the same altitude as that of our study. Additionally, Claydon et al (2004) and Hansen et al (2021) reported absolute data similar to those in our study in high-altitude residents, but unfortunately, they did not present data for a SL control group. It is possible that intoxication with cobalt from the surrounding cobalt mines augments hypoxia-mediated erythropoiesis ( Jefferson et al, 2002 ) and contributes to the excessive erythrocytosis described by Lawrence et al (1952) and Hurtado (1960) .…”
Section: Discussionsupporting
confidence: 65%
“…While the classic studies ( Lawrence et al, 1952 ; Hurtado 1960 ) and also Hansen et al (2021) and Claydon et al (2004) showed that high-altitude values were similar to sea-level values, Oberholzer et al (2020) found 28% lower PV values in residents at 3,800 m than in control subjects at SL. For CMS patients, the classic studies ( Lawrence et al, 1952 ; Hurtado 1960 ) found a marked reduction in PV by approximately 40%, which was much lower than those described by Hansen et al (2021) (−16%) and Claydon et al (2004) (−9%, nonsignificant). Oberholzer et al (2020) did not find any difference between the HH and CMS groups.…”
Section: Discussionmentioning
confidence: 77%
“…Although exercise fatigue and reduced exercise capacity have been commonly reported in CMS patients, allegedly due to systemic or pulmonary haemodynamic burden and O 2 -diffusion impairment as a consequence of excessive haematocrit and blood viscosity (Letcher et al, 1981;Monge, 1943;Ostergaard, 2020;Pratali et al, 2012;Soria et al, 2019;Stuber et al, 2010;Winslow & Monge-C, 1987), several studies indirectly suggest that adaptive mechanisms exist to maintain O 2 transport in the face of a high haematocrit (Juvonen et al, 1991;Lindenfeld et al, 1985). We have previously shown that Andeans diagnosed with mild to moderate CMS can attain normal maximal aerobic capacities compared to healthy Andean controls in Cerro de Pasco (4340 m) (Groepenhoff et al, 2012), and we have also recently confirmed these findings and identified evidence for an adaptive phenotype for O 2 transport during exercise with EE (Hansen et al, 2021).…”
Section: New Findingssupporting
confidence: 74%
“…One is pulmonary arterial hypertension during mild exercise, sometimes even at rest, indicating altered haemodynamics. It remains to be elucidated to what extent this is due to the increased blood viscosity in polycythaemia alone or by other maladaptive responses in severe CMS such as the increased sympathetic tone, which was even found in mild CMS in the present study (Hansen et al 2021). It would thus be of interest to expand these studies to severe polycythaemia and/or CMS to test these possibilities.…”
mentioning
confidence: 78%
“…In this issue of The Journal of Physiology, Hansen et al (2021) present very interesting results from an elaborate and difficult to perform study trying to explain how the cardiovascular system manages to bring the viscous blood of polycythaemic high-altitude residents to working skeletal muscle to prevent loss of performance capacity. The significance of this study lies in its widespread applicability to various clinical/pathological situations in which tissue hypoxia occurs by decreased arterial oxygen load and/or by impaired tissue supply.…”
mentioning
confidence: 99%